2008
DOI: 10.1586/17434440.5.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative monitoring of fluid responsiveness after esophageal surgery using stroke volume variation

Abstract: From May 2006, a new analyzing device (Vigileo monitor; Edwards Lifesciences LLC, Tokyo, Japan), which can be used in combination with the FloTrac and PreSep sensors, has been used in nine patients who have undergone radical operations for thoracic esophageal cancer at our hospital. Stroke volume variation (SVV), calculated for each respiratory cycle and displayed on the Vigileo monitor, precisely predicted intravascular hypovolemia. The maximum SVV of patients who needed fluid resuscitation was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Lopes et al (4) demonstrated that the GDT group received more fluid than the control group. The control group received fluid intraoperatively at the discretion of the anesthetist, according to the protocol proposed by Kobayashi et al (4).…”
Section: Discussionmentioning
confidence: 99%
“…Lopes et al (4) demonstrated that the GDT group received more fluid than the control group. The control group received fluid intraoperatively at the discretion of the anesthetist, according to the protocol proposed by Kobayashi et al (4).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that fluid therapies designed to achieve individualized and specific flow-related hemodynamic endpoints such as stroke volume or cardiac index (collectively referred to as goal-directed fluid therapy) may provide a superior alternative to fixed regimens or those based on static measures of cardiac filling, such as central venous pressure, which do not predict fluid responsiveness or correlate with circulating blood volume after transthoracic esophagectomy. 73,74 However, fluid responsiveness remains an elusive goal for managing patients ( Figure 5). As patients approach the upper inflection point of the Frank-Starling curve, small increases in cardiac output create large increases in lung water, and this effect is exacerbated in a situation of increased capillary permeability such as sepsis.…”
Section: Fluids Inflammation and The Glycocalyxmentioning
confidence: 99%
“…For example, central venous pressure does not predict fluid responsiveness or correlate with circulating blood volume after transthoracic oesophagectomy. 89,90 In addition to the potential importance of the amount and timing of fluid administration, there is some clinical evidence that the choice of fluid type may be important in affecting clinical outcomes. 91 Intravascular colloid retention during the treatment of hypovolaemia may approach 90% vs. 40% when administered during normovolaemia.…”
Section: Fluids Inflammation and The Glycocalyxmentioning
confidence: 99%